2015
DOI: 10.1039/c5gc00616c
|View full text |Cite
|
Sign up to set email alerts
|

A nano tetraimine Pd(0) complex: synthesis, characterization, computational studies and catalytic applications in the Heck–Mizoroki reaction in water

Abstract: Synthesis of a nano tetraimine Pd(0) catalyst system using an N,N-bisimine ligand and its catalytic applications in the Heck–Mizoroki reaction in water is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…In this study, ligand 3 was synthesized from 4‐chlorobenzaldehyde ( 1 ) and 1,2‐ethandiamine ( 2 ) in ethanol at room temperature. Ligand 3 was used for the synthesis of nano tetraimine Pd(0) complex 4 in the presence of Pd(OAc) 2 under nitrogen atmosphere in ethanol reflux (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, ligand 3 was synthesized from 4‐chlorobenzaldehyde ( 1 ) and 1,2‐ethandiamine ( 2 ) in ethanol at room temperature. Ligand 3 was used for the synthesis of nano tetraimine Pd(0) complex 4 in the presence of Pd(OAc) 2 under nitrogen atmosphere in ethanol reflux (Scheme ) …”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we have introduced a novel nano tetraimine Pd(0) complex as a heterogeneous catalyst for the Heck–Mizoroki coupling reaction of aryl halides with n ‐butyl acrylate in water . Herein, we describe another application of this heterogeneous nano tetraimine Pd(0) complex for the phosphine‐free Suzuki and copper‐free Sonogashira coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Heck-Mizoroki reaction has evolved significantly from its original mode as the arylation of olefins with aryl iodides, and the reaction has been further developed to allow the coupling of less reactive bromides, chlorides and pseudo-halides such as triflates, tosylates, mesylates, and aryl diazonium salts. [40][41][42][43] We used bromobenzene and styrene as the coupling partners to test the solvent and base effects in air (Table S2). Use of 1,4-dioxane as solvent and K 2 CO 3 as base gave trace coupling product at 110°C in 12 hr (entry 1).…”
Section: Catalytic Activity Of Nhc-pdcl 2 Species In the Heck-mizormentioning
confidence: 99%
“…[46][47] The combination of these two factors helps to stabilize the intermediate that forms during a catalytic process. [48] In continuing our efforts to study coupling reactions, [49][50][51] here we report the synthesis and characterization of a PdÀ P,N complex supported on three different functionalized supports such as MCM-41, SBA-16, and Fe 3 O 4 to investigate which of these supports provide better catalytic activity toward Oarylation reaction. Catalytic results showed that P,NÀ Pd-MCM-41 catalyst was more efficient for synthesizing diarylethers.…”
Section: Introductionmentioning
confidence: 99%